Effectiveness of manual therapy in temporomandibular disorders. Literature review - Ortiz, Geovanny (2022)
TMDs have important functional consequences, which do not distinguish age or gender. Treatment schemes are focused on improving function and relieving symptoms, they are mainly based on conservative therapies, avoiding over-treatment and at the same time, opportunely treating cases that require it, hence, avoiding more invasive treatments. Controlled studies on the efficacy of manual therapy for the treatment of TMDs are scarce, and the existing evidence has clear limitations in its methodology, despite this, it is the safest therapy although its results are controversial. Therefore, the aim of this work was to perform a literature review on the efficacy of manual therapy in the treatment of some temporomandibular disorders. In most of the studies it was noticed, the influence of professional advice and habit control talks in the treatment with manual therapy, as well as the consistency of the patients with their appointments, and the practice of at home exercises. The therapy proved to be effective in some of the TMDs, since in chronic cases, no significant improvement was evidenced.